Meningkatkan Prestasi Belajar Siswa Menggunakan Metode Demonstrasi Pada Materi Listrik - Idris, Idris (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title:  Improving Students' Learning Achievements Using Demonstration Methods on Electrical Material]. This study aims to improve the learning achievement of class VI Elementary School students in electrical materials using the demonstration method. This study is a Classroom Action Research (CAR) with the research subjects being class VI students of Sandik 2 Elementary School totalling 19 students. Formative test instruments on electrical material and observation sheets were used to collect data on student learning achievement and implementation of learning using the demonstration method. The results showed that 80% of the total students had reached 70% of the level of mastery of the concepts given. The results of the observations also show an active and well-functioning learning atmosphere. Based on the results of the study it can be concluded that the use of demonstration methods can improve student learning achievement on electrical material.